PENGARUH LATIHAN MENGGUNAKAN MEDICINE BALL OVERHEAD THROW TERHADAP HASIL POWER OTOT LENGAN DAN BAHU TIM BOLA BASKET SMP BINA MITRA WAHANA - Alparisman Alparisman; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Observation of the author when doing dribbling, passing and shooting activities there are still problems such as opponents who easily take over the ball that is being dribbled, the ball that will be passed on to friends often falls before getting caught friends, and not infrequently when doing ball shooting don't get to the ring. Though as stated above that dribbling, passing, and shooting are a series of solids in basketball. The purpose of this study was to determine the effect of exercise using medicine ball overhead throw on the results of the arm and shoulder muscle power of the Bina Mitra Wahana Middle School basketball team. The population to be used is 12 Bina Mitra Wahana middle school basketball players. The sample is simply interpreted as part of the population that is the actual data source in a study. In this study there was a population of 12 students. The instrument used in this research is two hand medicine ball put. The data obtained were analyzed using the t-test. Based on research conducted on 12 samples by doing a pre-test (initial test) the power of the arm and shoulder muscles. Then proceed with the treatment of medicine ball over head throw for 16 meetings, after which the muscles of the arm and shoulder muscles are tested. The average obtained from the results of the pretest posttest was 0.93, then the results obtained from the pretest and posttest were analyzed by t-test resulting in tcount of 2.435 with ttable 1.796 then accepted, at the alpha level (0.05. It can be concluded that there is the influence of medicine ball over head throw on the power of the arm and shoulder muscles in the Bina Mitra Wahana Middle School Basketball Team.Key Words: Medicine Ball Over Head Throw Exercises, Arm Muscles and Shoulder Power